Tingkat Kesejahteraan Pekerja Home Industri Tahu Tempe Di Kelurahan Ranomuut Kecamatan Paal Dua Kota Manado - Harahap, Monika Aprillia; Lumingkewas, Jelly Ribka Danaly; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2023)
This study aims to determine and see the Welfare Level of Workers in the Tofu and Tempe Home Industry (Case Study: Home Industry in Ranomuut Village, Paal Dua District, Manado City). This research was conducted from August to October 2022. Sampling used a purposive sampling method. Data collection was obtained through direct interviews with the help of questionnaires to 9 respondents using concepts and indicators from the 2015 version of the National Population and Family Planning Agency (BKKBN) which includes 5 stages of family welfare indicators. Data analysis used descriptive analysis methods by making tables and percentages to explain the level of welfare of workers in the tofu and tempeh home industry, Ibu Enda, in Ranomuut sub-district, Paal Dua sub-district. The results showed that most workers in the tofu and tempeh home industry fall into the category of prosperous families I (KS I) and prosperous families II (KS II).